2014
DOI: 10.1038/bmt.2013.233
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine salvage therapy for relapse of myeloid malignancies following allogeneic hematopoietic SCT

Abstract: Patients with hematopoietic malignancies relapsing after allogeneic hematopoietic SCT (allo-HSCT) have a poor prognosis. We retrospectively analyzed the patients who received azacitidine in our center in the course of treatment of their post-transplant relapse. We identified 31 patients. Relapse occurred at a median of 3.7 (1.7-37.6) months following allo-HSCT. Patients received a median number of three cycles (1-12) of azacitidine (7 days, 75 mg/m 2 daily). Thirty-nine percent of patients had either a monosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 27 publications
5
51
1
2
Order By: Relevance
“…The CR rate of 9.7% in this analysis was lower than that in other studies with this approach, for example, Tessoulin et al 23 (CR 14%, overall response rate (ORR) 29%), Schroeder et al 6 (CR 23%, ORR 30%) and Czibere et al 5 (CR 23%, ORR 72%). One possible reason for this is the lower dosage (2, 3 or 4 days) of 5-azacytidine 100 mg per day, which 75% of our patients received as a starting dose.…”
Section: Discussioncontrasting
confidence: 48%
“…The CR rate of 9.7% in this analysis was lower than that in other studies with this approach, for example, Tessoulin et al 23 (CR 14%, overall response rate (ORR) 29%), Schroeder et al 6 (CR 23%, ORR 30%) and Czibere et al 5 (CR 23%, ORR 72%). One possible reason for this is the lower dosage (2, 3 or 4 days) of 5-azacytidine 100 mg per day, which 75% of our patients received as a starting dose.…”
Section: Discussioncontrasting
confidence: 48%
“…Table 1 summarizes the publications regarding the use of Aza as salvage treatment for relapse after allo-SCT: until now a total of 601 patients with AML, MDS and other related myeloid malignancies have been published with varying schedules and dosages of Aza. These included 3 prospective, non-randomized trials and the majority of patients reported retrospectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Furthermore, Aza was the first treatment of relapse and combined with DLI in some of these patients, while other patients had previously received other salvage therapies or did not receive DLI.…”
Section: Azacitidine For the Treatment Of Relapsementioning
confidence: 99%
“…8,9 A number of small series have reported that AZA can induce remissions in patients who relapse after an allogeneic transplant, raising the possibility that this agent represents a potential new treatment strategy in this challenging patient population. [10][11][12] Furthermore, it has been suggested in single arm studies that AZA may augment the anti-tumor activity of DLI in patients who relapse after an allograft. 13 However, importantly, so far there has been no systematic analysis of the clinical activity of AZA in patients who have relapsed after an allograft for AML or MDS, or of whether its activity is increased by the concurrent administration of DLI.…”
Section: Clinical Activity Of Azacitidine In Patients Whomentioning
confidence: 99%
“…Prospective studies to confirm optimal treatment options in this challenging patient population are required. relapse after allogeneic stem cell transplantation for acute myeloid leukemia Charles Craddock, 1 Myriam Labopin, 2 Marie Robin, 3 Juergen Finke, 4 Patrice Chevallier, 5 Ibrahim Yakoub-Agha, 6 Jean Henri Bourhis, 7 Henrik Sengelov, 8 Didier Blaise, 9 Thomas Luft, 10 Michael Hallek, 11 Nicolaus Kröger, 12 Arnon Nagler, *13 and Mohamad Mohty developing effective treatment options for patients with recurrent disease after allogeneic SCT, and the great majority remain destined to die of resistant disease. 3 Although a small number of patients with disease recurrence can survive long term after a second transplant or donor lymphocyte infusion (DLI), the success of both these treatment modalities is contingent on the prior acquisition of morphological remission with salvage therapy.…”
mentioning
confidence: 99%